2003
DOI: 10.1046/j.1463-6395.2003.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and systematic affinity ofStanleya neritinoides(Smith, 1880), an enigmatic member of the thalassoid gastropod species flock in Lake Tanganyika, East Africa (Cerithioidea, Paludomidae)

Abstract: The radiation of gastropods in Lake Tanganyika is an ideal system for testing competing hypotheses of species flock formation. Yet, much of the basic biology of these species remains unknown. In an ongoing effort to understand the evolution of Tanganyikan gastropods, we here describe Stanleya neritinoides. Alcohol‐preserved material of the soft parts is rare, consequently, the systematic position of the species, and a repeated suggested affinity to Tanganyicia rufofilosa, have been based primarily on features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…This finding, which has recently been supported by molecular data , renders previous taxonomy-dependent speculations -whether there is, for example, an intrinsic proneness to radiate in 'thiarids' (Michel, 1994)superfluous. In addition, detailed studies of individual taxa within this species flock, such as Tanganyicia (Strong & Glaubrecht, 2002) and Stanleya (Strong & Glaubrecht, 2003) have revealed a far greater diversity of reproductive modes than assumed hitherto. The implications of these new data for interpretation of the adaptive radiation of the Lake Tanganyika gastropods are wide-ranging, given that viviparity has long been considered one of the decisive factors in molluscan adaptive radiations in ancient lakes Michel, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This finding, which has recently been supported by molecular data , renders previous taxonomy-dependent speculations -whether there is, for example, an intrinsic proneness to radiate in 'thiarids' (Michel, 1994)superfluous. In addition, detailed studies of individual taxa within this species flock, such as Tanganyicia (Strong & Glaubrecht, 2002) and Stanleya (Strong & Glaubrecht, 2003) have revealed a far greater diversity of reproductive modes than assumed hitherto. The implications of these new data for interpretation of the adaptive radiation of the Lake Tanganyika gastropods are wide-ranging, given that viviparity has long been considered one of the decisive factors in molluscan adaptive radiations in ancient lakes Michel, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In a first molecular analysis, West & Michel (2000) favour the paraphyly of the thalassoid gastropods identifying five clades which they assign to the Thiaridae: within group 1, with Reymondia and Spekia, they also found Cleopatra (as non-endemic "outgroup" used), group 2 with Stanleya and Tanganyicia as sister to the former (which is evidently not the case; see details in Strong & Glaubrecht 2003), group 3 with Bathanalia, Chytra and Limnotrochus, group 4 (Lavigeria) and group 5 with Paramelania and Anceya. From their analysis, they concluded that the thalassoid gastropods form a "superflock" or group of closely related endemics that have radiated rapidly and in situ in Lake Tanganyika.…”
Section: Discussionmentioning
confidence: 99%
“…-Taxa with paucispiral to entirely spiral operculum: This operculum is reported to occur in Stanleya, Mysorelloides, Bathanalia, Limnotrochus and Chytra (cf. Pilsbry & Bequaert 1927;Brown 1994;Strong & Glaubrecht 2003). It is also present in Syrnolopsis, Anceya and Martelia, where it is very thin and translucent (Strong & Glaubrecht 2008).…”
Section: Character Evaluationmentioning
confidence: 99%
“…Other anatomical modifications in syrnolopsines occur sporadically among some but not all small species (L‐shaped crescentic ridge in the midgut) and occasionally occur in some large species as well (short lateral extensions on lateral teeth, short salivary glands, midgut caecum lacking) (Strong and Glaubrecht 2002, 2003, 2007). The taxonomic distribution of these characters and character states does not necessarily falsify the hypothesis that these features evolved as a consequence of reduction in size.…”
Section: Discussionmentioning
confidence: 99%
“…The spermatophore‐forming organs of A. giraudi and S. lacustris differ in that the former is similar to that of other Lake Tanganyika paludomids (see e.g. Strong and Glaubrecht 2002, 2003; Glaubrecht and Strong 2004), while that of the latter has been reduced to a small rounded pouch. Additionally, the aperture allowing communication between the mantle cavity and gonoduct is much smaller in S. lacustris .…”
mentioning
confidence: 89%